Monotherapy for low-risk gestational trophoblastic neoplasia with score 5-6 - Kemin, Li; Mengpei, Zhang; Rutie, Yin (Frontiers in Oncology, 2022)
Objective: To investigate the monotherapy for gestational trophoblastic neoplasia (GTN) patients with FIGO/WHO prognostic score of 5–6. Methods: The low-risk GTN patients from 2012 to 2019 were enrolled. The study is a retrospective report to analyze the efficacy and safety of single-agent chemotherapy and combination chemotherapy in patients with a high FIGO/WHO prognostic score of 5–6. Results: 75 cases (33.5%) were included. Complete remission was in all patients. Among the 29 cases taking single-agent chemotherapy, 22 cases (75.9%) developed drug resistance. Among the 46 cases taking combination chemotherapy, 7 patients (15.2%) developed drug resistance. There was a statistically significant difference in the drug resistance rate between these two subgroups (P < 0.05), but there was not statistically significant difference in the total number of chemotherapy courses (<2mIU/ml) (P < 0.05). Conclusion: Monotherapy showed remarkable advantages in GTN patients with FIGO/WHO prognostic score of 5–6.